Crenicichla tesay, a new species of cichlid (Perciformes: Labroidei) from the río Iguazú basin in Argentina - Casciotta, Jorge Rafael (2008)
Crenicichla tesay, a new species of cichlid (Perciformes: Labroidei) from the río Iguazú basin in Argentina. - Crenicichla tesay sp. n. differs from its congeners by the following combination of characters: posterior border of preopercle serrated, 48-59 scales on El row, snout length 2.6-2.8 times in head length, presence of conspicuous suborbital stripe, flanks with 4 to 6 blotches below the upper lateral line, posteriormost blotch extending on caudal peduncle. Colour pattern with numerous irregularly scattered dots, and absence of vertical stripes on flanks.